Developmental Conflict and its Impact on Biodiversity of Pench National Park, Maharashtra, India - Chaturvedi, Alka; Phani Kumar, G. (Indian Forester, 2006)
For purposes of studying the impact of developmental activities and tourism on Pench National Park, the entire Park has been divided into three zones : (i) area adjacent to the village boundary and allowed use of NTFPs by the villagers; (ii) area open to tourism, and (iii) core area. The results indicate that peoples' proximity to the reserved areas does not affect the biodiversity much as their dependence on forests is limited to NTFPs only. Biodiversity is negatively affected by tourism pressures and developmental activities such as construction of roads, dams which cause disturbance to the biota of the area.